Stakeholder Role Analysis in Mangrove Ecosystem Management in Lembar Selatan Village, West Lombok - Islam, Saiful; Jupri, Ahmad; Isrowati, Isrowati; Ahyadi, Hilman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Mangrove ecosystems provide ecological and economic services but are increasingly threatened by land conversion, overexploitation, and weak governance coordination. In Lembar Selatan Village, West Lombok, about 57% of the mangrove area has been degraded despite ecotourism-based management initiatives. This study aimed to identify stakeholders and analyze their roles in mangrove ecosystem management. Data were collected through structured in-depth interviews with 14 purposively selected respondents representing government agencies, community groups, tourism actors, academics, and civil society organizations. The interest and influence variables for each stakeholder were measured on a scale of 1 to 5, with the combined total scores categorized into five priority levels. These quantitative outputs were then utilized to analyze stakeholder roles through an interest-influence matrix. The results showed that 14 stakeholders were involved and grouped into three categories. Subjects comprised, fishermen, travel operators, NGOs, MSMEs, the village head, hamlet heads Polairud, West Lombok Marine and Fisheries Office, and KLHK NTB; these actors had high interest but limited influence. Key players included BKSDA NTB, West Lombok Tourism Office, BAPPEDA West Lombok and Pokdarwis. Bystanders consisted of academics. The study indicates that stronger coordination between high-influence institutions and community-based actors is essential to improve sustainable mangrove management in Lembar Selatan.